Modification of Banten Cultural Ethnomathematics Monopoly Game Using the ADDIE Model on Flat Shape Material in Grade IV Elementary School - Yuniar, Silfania; Arisetyawan, Andika (Educationist: Journal of Educational and Cultural Studies, 2022)
The background of this study by the lack of understanding and students' interest in learning about the concepts of flat waking that result in less-than-optimal student learning. Because of the still conventional learning process, teachers seldom use learning media so as to make math lessons seem monotonous, boring, and uninteresting, and difficult for students to understand. With this need for proper use and force to study media for students. With modified Banten culture monopoly playing as an alternative to the study media for fourth grade. The method used in this study is a conceptual analysis involving a qualitative approach using ethnographic methods was selected because studies were intended generally to know baduy society and integrate it into a game of antipoppy as a medium of learning using ADDIE model through 5 stages (1) analyze stage, (2) design stage, (3) development stage, (4) implementation stage, (5) evaluation stage, Banten culture based media monopoly is designed according to the need of the learning curriculum, which can increase students' understanding of the space and cultural building in Banten. Banten culture-based monopoly received excellent responses from some of the students who had used it. The results of this study are recommended for elementary school teachers, and for future researchers.